Silastic Foam Elastomer for Dressing Open Granulating Wounds—A Preliminiary Report - Kumar, Sandeep; Ramakant, Ramakant; Bhattacharya, Surajit; Sinha, K. N.; Dubey, P. C. (Indian Journal of Plastic Surgery, 1987)
A preliminary report on the utility of silastic foam elastomer in the management of 32 open granulating wounds in 30 patients is presented. By offering more wound comfort to the patients and by relieving the work load of surgical residents and nurses, the silicone stent serves a dual function. The ease with which the patients can dress themselves makes such a dressing ideal for domiciliary practice. The cost of silastic foam elastomer may well balance the cumulative cost of conventional dressing material i.e. cotton gauze and bandages and their sterilization.